Urban transport in the developing world a handbook of policy and practice - Dimitriou, Harry T.; Gakenheimer, Ralph Albert; Edward Elgar Publishing (Cheltenham ; Northhampton, Mass. : Edward Elgar, 2011)
The twenty thematic chapters in this book provide a broad set of perspectives on the plight, possibilities and opportunities of urban transport in the developing world, set against the challenges of sustainable development. The contributors expertly set the international context of transport policy-making and planning for developing cities and present a critical review of recent developments that have taken place and which offer lessons for the future.
Transport and city development : understanding the fundamentals / Harry T. Dimitriou -- Land use and transport in rapidly motorizing cities : contexts of controversy / Ralph Gakenheimer -- An international comparative perspective on fast-rising motorization and automobile dependence / Jeffrey Kenworthy -- The future of energy for urban transport / Andreas Schäfer -- Environmental challenges of urban transport : the impacts of motorization / John Ernst -- Economic fall-out of failing urban transport systems : an institutional analysis / Elliott Sclar and Julie Touber -- Non-motorized urban transport as neglected modes / V. Setty Pendakur -- Poverty and urban mobility : diagnosis toward a new understanding / Xavier Godard -- Institutional and political support for urban transport / Edward Dotson -- Environmental evaluation in urban transport / Michael Replogle -- Equity evaluation of urban transport / Eduardo A. Vasconcellos -- Use and abuse of economic appraisal of urban transport projects / Walter Hook -- Road crashes and low-income cities : impacts and options / Any Aeron-Thomas and Goff Jacobs -- Bus rapid transit : a review of recent advances / Lloyd Wright -- Rail rapid transit advances / Roger J. Allport -- Informal public transport : a global perspective / Robert Cervero and Aaron Golub -- Options for travel demand management : traffic bans versus pricing / Anjali Mahendra -- Mainstreaming sustainable urban transport : putting the pieces together / Christopher Zegras -- Conclusions : emergent crucial themes / Harry T. Dimitrou and Ralph Gakenheimer.
Includes bibliographical references and indexes.
Keywords: Urban transportation policy -- Developing countries; Electronic books